PRODUCTION OF METAL-BASED IMPLANTS FOR CYRO-FACIAL INJURIES (BLUEPRINTS) - LIM , SlOW LING (Universiti Teknologi Petronas, 2004)
The main objective of this project is to propose a design for a progressive die for the production of metal based implants for Cyro-facial injuries. The bulk of the work would be to produce the detailed design drawings or blueprints for each progressive die components and to suggest the appropriate process plans for the fabrication of the respective progressive die components. The main concentration is put in producing the blueprint~ of a progressive die to produce the I-shaped metal implants. Throughout the first semester, literature reviews are done to gain knowledge about the working principle of the progressive die and how to design the various die components needed in the progressive die. Other than that, literature reviews are also done to gain information about the minimum tolerances, clearances and angular relief that need to be applied to each die components to ensure the quality of the progressive die and also the metal implants that will be produced by the progressive die. The basic step in producing a progressive die is to produce the blank layout. There are many ways in laying out the scrap strip. However, for this particular project, the blanks are laid out by adopting the narrow-run, one-pass layout. To optimize the usage of the material strip while ensuring the quality of the produced implants, minimum bridge allowances are applied between blanks and between blanks and edges of the strip. After calculation, the blanking force needed to cut the blank from the strip is 33707.52 N and since the press capacities are usua:lly in tons, a press of more than 3. 789 tons should be chosen to produce this particular metal implants. Other than that, it is also found that, a total of 63 metal implants can be produced from a 1 m material strip. On the other hand, in designing the die components, care had been taken in assigning the correct clearances, angular relief, allowances and tolerances for each part of the die components. This is to ensure the success of the particular progressive die. In general, the material selected for the implants are titanium and stainless steel strips while for the die components, are tool steels, mild steel and cast steel. The main processes involved for fabricating the die components are Wire EDM and milling.